2013
DOI: 10.1186/1746-1596-8-64
|View full text |Cite
|
Sign up to set email alerts
|

A juvenile case of conjunctival atypical nevus

Abstract: Virtual slidesThe virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/2973228795724608Melanocytic nevi are the most common tumors of the conjunctiva, accounting for 28% of all neoplastic lesions. These tumors, despite their benign behavior, share some atypical histological features with nevi found in other anatomic sites like the genital and acral regions, globally designated as nevi with site-related atypia. Moreover, in children and adolescents, rapidly growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Colarossi et al (8) observed that during growth and puberty, conjunctival lesions are often surrounded by inflammation, which mimics an increase in size and thus might raise a suspicion of malignancy. In the study by Aalkatan et al 4, histological findings of conjunctival pigmented nevi were studied separately in a subgroup of patients below 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Colarossi et al (8) observed that during growth and puberty, conjunctival lesions are often surrounded by inflammation, which mimics an increase in size and thus might raise a suspicion of malignancy. In the study by Aalkatan et al 4, histological findings of conjunctival pigmented nevi were studied separately in a subgroup of patients below 20 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of malignant conjunctival melanoma is extremely low in children. According to several authors, conjunctival nevus undergoes malignant transformation in only 1% of cases (1,3,8,9). There are only 29 reported cases of conjunctival melanoma in children aged 15 years or younger (4,11,14,15), and only 9 cases have been well-documented and described in detail.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations